2018
DOI: 10.1002/ange.201812142
|View full text |Cite
|
Sign up to set email alerts
|

Building from Ga‐Porphyrins: Synthesis of Ga‐Acetylide Complexes Using Acetylenes and Polyynes

Abstract: Multidimensional, conjugated building blocks have been formed through the axial coordination of polyynes to the central Ga atom of tetraarylporphyrins. Electron deficient pentafluorophenyl substituents in the meso‐positions provide more stable σ‐acetylide complexes to Ga than analogous structures with tert‐butylphenyl groups. Mono‐, di‐, and triynes have been used, including a pyridyl endcapped diyne that allows for formation of porphyrin triads through coordination of the pyridyl ligand to a Ru porphyrin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…It is noted that the incorporation of perfluorophenylgroups in the meso-positions of the porphyrini ncreases persistence of the resulting complexes in comparison to nonfluorinated arenes, as ar esult of as tronger metal-acetylide bond. [10] As am odel compound for comparison to GaL1 that does not contain the coordinating pyridyl ligand,complex GaL2 was prepared in 93 %y ield via lithiation of trans-L2 with nBuLi and addition to porphyrin 5 in as olutiono ft oluene. Both compounds, GaL1 and GaL2 are stable solids that slowly hydrolyze in solution to liberate the free azo ligand, presumably due to the presence of adventitious water.…”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…It is noted that the incorporation of perfluorophenylgroups in the meso-positions of the porphyrini ncreases persistence of the resulting complexes in comparison to nonfluorinated arenes, as ar esult of as tronger metal-acetylide bond. [10] As am odel compound for comparison to GaL1 that does not contain the coordinating pyridyl ligand,complex GaL2 was prepared in 93 %y ield via lithiation of trans-L2 with nBuLi and addition to porphyrin 5 in as olutiono ft oluene. Both compounds, GaL1 and GaL2 are stable solids that slowly hydrolyze in solution to liberate the free azo ligand, presumably due to the presence of adventitious water.…”
Section: Synthesismentioning
confidence: 99%
“…[26] X-ray analyses X-ray crystallographic analysish as been successful for RuL1 and RuL4Ru,c onfirming both the proposed structure and stereochemistry about the azo moiety ( Figure 1). In both molecules, the Ru-porphyrin features slightly distorted, six-coordinate octahedralg eometry.T he carbon and nitrogen framework of porphyrin ring is essentiallyp lanar in both cases, and the mean deviations from the least-squares planes( porphyrin-N,N,N,N-plane) fall within the range of À0.106 (9) to 0.078 7for RuL1 and À0.220 (5) to 0.039(4) for RuL4Ru.T he Ru atom is situated above this plane by 0.061(2) and 0.0718 (10) for RuL1 and RuL4Ru,r espectively.T he axial pyridyl ligandsa re close to perpendicular to the porphyrin rings with N(py)-Ru-N(pyrrole) angles ranging from 87.61 (16) to 88.74 (16)8 for RuL1 and8 6.12(8)8 to 89.31(8)8 for RuL4Ru.F urthermore, the N(py)-Ru-C(CO) angles of RuL1 and RuL4Ru are nearly linear at 177.6(2) and 179.22(11)8,r espectively.W ith respectt ot he ligand,t he dihedrala ngle between the pyridyl and the phenylene ring of trans-L1 is only 13.9(2)8,w hile the two pyridyl rings of trans-L4 are coplanar (as determined by planes generated from the six atoms of the aryl groups of the linkers). Finally,t he solid-state structuresh ighlightt hat the presence of the CO ligand complicates the use of Ru-porphyrins as part of a platform strategy,a lthough the photochemical removal of the CO group is possible (see below).…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27][28] This situation is observed in organic compounds, as well as in some of the metal complexes, although not many studies aimed to explain the observed patterns. [29][30][31][32][33] [22][23][24] The preference for the fluoroarene-alkyne interaction over the fluoroarene-arene interaction has also been observed in macrocyclic structures. For example, Bunz and co-workers observed that the cocrystal of hexafluorobenzene and the cyclic dimer of orthodiethynylbenzene shows a stacking pattern in which hexafluorobenzene centers above the alkyne moieties rather than the benzene rings of the macrocycle.…”
mentioning
confidence: 97%